2017
DOI: 10.1007/s10637-017-0457-9
|View full text |Cite
|
Sign up to set email alerts
|

MPT0B002, a novel microtubule inhibitor, downregulates T315I mutant Bcr-Abl and induces apoptosis of imatinib-resistant chronic myeloid leukemia cells

Abstract: Chronic myeloid leukemia (CML) is a hematopoietic malignancy caused by the constitutive activation of Bcr-Abl tyrosine kinase. The Bcr-Abl inhibitor imatinib and other second-generation tyrosine kinase inhibitors such as dasatinib and nilotinib have remarkable efficacy in CML treatment. However, gene mutation-mediated drug resistance remains a critical problem. Among point mutations, the Bcr-Abl T315I mutation confers resistance to these Bcr-Abl inhibitors. Previously, we have synthesized the compound (1-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…We previously showed that MPT0B169 and MPT0B002 are tubulin inhibitors that disrupt tubulin polymerization in leukemia cells [9,10]. Therefore, we examined the effects of MPT0B169 and MPT0B002 on tubulin polymerization in COLO205 and HT29 cells.…”
Section: Mpt0b169 and Mpt0b002 Inhibit Tubulin Polymerizationmentioning
confidence: 98%
See 4 more Smart Citations
“…We previously showed that MPT0B169 and MPT0B002 are tubulin inhibitors that disrupt tubulin polymerization in leukemia cells [9,10]. Therefore, we examined the effects of MPT0B169 and MPT0B002 on tubulin polymerization in COLO205 and HT29 cells.…”
Section: Mpt0b169 and Mpt0b002 Inhibit Tubulin Polymerizationmentioning
confidence: 98%
“…Our previous study showed that MPT0B169 and MPT0B002 can inhibit the proliferation of leukemia cells [9,10]. Herein, to examine the effects of MPT0B169 and MPT0B002 on the cell viability of solid tumor cells, the U87MG and GBM8401 glioblastoma cells, MCF-7 and MDA-MB-231 breast cancer cells, A549 lung cancer cells, COLO205 and HT29 CRC cells were incubated with an increasing concentration of MPT0B169 (0.1-10 μmol/L) or MPT0B002 (0.01-10 μmol/L) for 48 h. Cell viability was determined with an MTT assay.…”
Section: Mpt0b169 and Mpt0b002 Are More Effective On Colo205 And Ht29mentioning
confidence: 99%
See 3 more Smart Citations